Training proposals for the Italian education system - Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2021)
In the Digital Economy and Society Index (DESI) ranking, Italy fell two places this year on the digital skills possessed by human capital. The Italian trend from 2015 to today, according to DESI, portrays a substantial stagnation in digital skills over time. Training therefore proves to be an essential lever for reversing this trend. For this reason, training is meant here in all its articulations (continuous training, managerial training, organised by Professional Orders, on-line training carried out by hardware and software manufacturers and other training proposals), and throughout life (Life Long Learning - LLL), but also in relation to the training proposals of the Italian educational system, Istruzione e Formazione Tecnica Superiore (IFTS) and Istituti Tecnici Superiori (ITS) established in 2006, which, in the Italian system, represent the alternative training channel to the university system, with a distinctive professionalising purpose.